2006
DOI: 10.1038/sj.ijir.3901476
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of sildenafil failures with cabergoline: a randomized, double-blind, placebo-controlled study

Abstract: To evaluate the safety and efficacy of cabergoline in men with erectile dysfunction (ED) who did not respond to sildenafil. Four hundred two sildenafil nonresponders aged from 21 to 59 years were included in the study. Patients were randomly divided into group 1, those who received 0.5-1 mg cabergoline weekly for 6 months and group 2, who received placebo for the same period. They underwent preliminary assessment, including medical and sexual history, self-administered International Index of Erectile Function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 71 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…It is estimated that up to 30%–40% of patients do not respond sufficiently to PDE-5 inhibitor therapy 96. A randomised clinical trial found that 31.2% of sildenafil non-responders responded to cabergoline, while only 7.1% of patients responded within the placebo group 97. There is evidence that diabetes affects the central dopaminergic pathways, resulting in increased rates of ED and Parkinson’s disease 98.…”
Section: Anti-parkinsonian Drugsmentioning
confidence: 99%
“…It is estimated that up to 30%–40% of patients do not respond sufficiently to PDE-5 inhibitor therapy 96. A randomised clinical trial found that 31.2% of sildenafil non-responders responded to cabergoline, while only 7.1% of patients responded within the placebo group 97. There is evidence that diabetes affects the central dopaminergic pathways, resulting in increased rates of ED and Parkinson’s disease 98.…”
Section: Anti-parkinsonian Drugsmentioning
confidence: 99%
“…8,9 Sildenafil's efficacy is also lower in patients with some risk factors and diseases such as diabetes mellitus, 10,11 hypertension, 12 multiple sclerosis 13 and combat-related posttraumatic stress disorder. 14 Centrally acting drugs, such as dopamine agonists 15 and melanocortin analog, 16 have been used as less invasive modalities (vs intracavernous injection, vacuum constrictive device and penile prosthesis) with various success rates to salvage sildenafil nonresponders. However, the growing numbers of men with ED, and the significant number of patients for whom this treatment is ineffective or contraindicated, make sildenafil nonresponders a great challenge for urologists.…”
Section: Introductionmentioning
confidence: 99%
“…The instruction sheet emphasized its use on an empty stomach, the proper timing of sildenafil administration (30 min-2 h before sexual attempt) and the absolute need for appropriate sexual stimulation. Erectile function was categorized as follows using the 5-item version of the International Index of Erectile Function (IIEF-5) total scores: no ED (22)(23)(24)(25), mild ED (17-21), mild to moderate ED (12)(13)(14)(15)(16), moderate ED (8-11) and severe ED (5-7). 30,31 Participants were further categorized into five age groups according to their age: 18-30, 31-40, 41-50, 51-60 and 61-70.…”
Section: Introductionmentioning
confidence: 99%
“…However, combination therapy was associated with a 33% incidence of adverse effects, including a 20% incidence of dizziness side effects (McMahon et al 1999). Finally, preliminary data suggest a possible role for combination treatment with cabergoline (Safarinejad 2006) or statins (Herrmann et al 2006; Osborne 2006) in non-responders to sildenafil alone.…”
Section: Management Strategy For Treatment Failuresmentioning
confidence: 99%